2012
DOI: 10.1007/s11665-012-0273-5
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical Behavior of a 25Cr Super Duplex Stainless Steel at Elevated Temperature

Abstract: Super duplex stainless steel (SDSS) is a candidate material for production tubing in oil and gas wells and subsea pipelines used to transport corrosive hydrocarbon fluids. The suitability of this material for high temperature applications is examined in this paper. The uniaxial tensile properties are determined for a 25Cr super duplex stainless steel over a range of temperature relevant to high pressure-high temperature oil and gas wells. It is shown that there is a significant effect of temperature on the uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The volume fractions of carbides, austenite and ferrite predicted through Thermo-Calc software showed consistent results with experimental fractions of the phases obtained in alloy structure [15]. Many research works have reported the effects of heat treatment on the impact of strength, corrosion and microstructure features of DSS [11,17]. Pressurized fluid flow pipes, tubes, pumps, transmitters, etc.…”
Section: Introductionsupporting
confidence: 61%
“…The volume fractions of carbides, austenite and ferrite predicted through Thermo-Calc software showed consistent results with experimental fractions of the phases obtained in alloy structure [15]. Many research works have reported the effects of heat treatment on the impact of strength, corrosion and microstructure features of DSS [11,17]. Pressurized fluid flow pipes, tubes, pumps, transmitters, etc.…”
Section: Introductionsupporting
confidence: 61%
“…The uniaxial strain at the onset of plastic yielding of the SDSS material under consideration at the test temperature of 90 °C was found to be 0.3% . The applied axial stress of 568 MPa was below the elastic limit, however, for internal pressure only and combined loading, the pipe was stressed beyond the elastic limit but below the level that caused burst or failure, see Figure .…”
Section: Resultsmentioning
confidence: 93%
“…The ferrite and austenite ratio were 49 and 51%, respectively. The mechanical properties of the material are presented elsewhere . For completeness, the effects of temperature on the Young's modulus, yield strength, and the ultimate tensile strength of the material are shown in Table .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed growing interest of the maritime industry and the extraction industry of oil and natural gas in Cr-Ni duplex steels (DSS, SDSS) and cast steels was mainly due to their good, compared to austenitic steels (AISI 304, 316), mechanical, corrosion [2][3][4][5] and erosioncorrosion properties [6÷8]. This is particularly important in the case of storage tanks for gas and oil, which during use are exposed not only to the effect of corrosive media, but also to the high pressure (69÷207 MPa) and temperature (149÷260 C) [9].…”
Section: Introductionmentioning
confidence: 99%